PKC‐θ exists in an oxidized inactive form in naive human T cells. Issue 6 (12th April 2013) - von Essen, Marina Rode; Kongsbak, Martin; Levring, Trine Bøegh; Hansen, Ann Kathrine; Boding, Lasse; Lauritsen, Jens Peter Holst; Woetmann, Anders; Baier, Gottfried; Ødum, Niels; Bonefeld, Charlotte Menné; Geisler, Carsten
<x xml:space="preserve">Abstract</x> PKC‐θ plays a central role in TCR‐induced IL‐2 production and T‐cell proliferation. The aim of the present study was to analyse how PKC‐θ is regulated in human T cells during T‐cell activation and differentiation. We show that PKC‐θ is found in a high‐molecular disulfide‐linked complex in naïve T cells, and that PKC‐θ most likely is inactive in this form. In parallel with the accumulation of the major redox regulators, glutathione and thioredoxin, PKC‐θ is gradually reduced to the 82 kDa active form during T‐cell activation. We demonstrate that PKC‐θ is recruited to the plasma membrane in the disulfide‐linked form in naïve T cells, and that activation of PKC‐θ is redox dependent and requires de novo synthesis of glutathione. This is the first study that shows that the activity of PKC‐θ is regulated by the intracellular redox state, and that PKC‐θ is recruited to the plasma membrane in an inactive form in naïve T cells. Our observations underscore the existence of major differences in TCR signaling in naïve versus primed T cells.